Effect of TCNQ Layer Cover on Oxidation Dynamics of Black Phosphorus. Issue 8 (29th May 2018) - Meingast, Laura; Koleśnik‐Gray, Maria; Siebert, Martin; Abellán, Gonzalo; Wild, Stefan; Lloret, Vicent; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Krstić, Vojislav
Abstract : The puckered surface of black phosphorus represents an ideal substrate for an unconventional arrangement of physisorbed species and the resulting specific two‐dimensional chemistry of this system. This opens the way to investigate the chemical and physical properties of locally confined areas of black phosphorus without the necessity for further physical downscaling of the material. We have evaporated tetracyanoquinodimethane (TCNQ) on top of black phosphorus under over‐saturation non‐equilibrium conditions in vacuum. The evolution of linear density and height of droplets formed through oxidation during exposure to air is studied time dependently by scanning‐force microscopy. Our study suggests that the TCNQ molecules spontaneously arrange in a thin layer of the order of a few nm height, which, however, is fragmented with a periodicity of about 100 nm. It is shown that within the confined space separating the layer fragments the chemical dynamics of the oxidation process is remarkably different than on a bare black phosphorus surface. Abstract : The oxidation dynamics in electrostatically confined areas of black phosphorus is different than in extended black phosphorous surfaces. Such areas can be achieved by evaporation of a nm thick tetracyanoquinodimethane (TCNQ) layer on top of black phosphorus under over‐saturation non‐equilibrium conditions. This unconventional arrangement of physisorbed species is attributed to black phosphorus' puckered surface.